Characterizing Individual Differences in Sweet Taste Hedonics: Test Methods, Locations, and Stimuli - Cheung Mayh M; Kramer Matthwe; Beauchamp Gary K; Puputti Sari; Wise Paul M (MDPI, 2022)
Sweetness drives the consumption of added sugars, so understanding how to best measure sweet hedonics is important for developing strategies to lower sugar intake. However, methods to assess hedonic response to sweetness vary, making results across studies difficult to integrate. We compared methods to measure optimal sucrose concentration in 21 healthy adults (1) using paired-comparison preference tracking vs. ratings of liking, (2) with participants in the laboratory vs. at home, and (3) using aqueous solutions vs. vanilla milk. Tests were replicated on separate days to assess test-retest reliability. Test-retest reliability was similar between laboratory and home testing, but tended to be better for vanilla milk and preference tracking. Optimal sucrose concentration was virtually identical between laboratory and home, slightly lower when estimated via preference tracking, and about 50% lower in vanilla milk. However, optimal sucrose concentration correlated strongly between methods, locations, and stimuli. More than 50% of the variability in optimal sucrose concentration could be attributed to consistent differences among individuals, while much less variability was attributable to differences between methods. These results demonstrate convergent validity between methods, support testing at home, and suggest that aqueous solutions can be useful proxies for some commonly consumed beverages for measuring individual differences.